1999
DOI: 10.1089/jwh.1.1999.8.1195
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Need for Faculty Development in Women's Health among Internal Medicine and Family Practice Teaching Faculty

Abstract: Women's health education is an emerging interdisciplinary field that has recently received national attention. The American Board of Internal Medicine and the American Academy of Family Practice recently have published competencies in women's health for their residents, with increased attention to gynecological and mental health issues. Increasing women's health in the curricula of internal medicine (IM) and family practice (FP) residents will certainly require faculty development among IM and FP teaching facu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 8 publications
(2 reference statements)
0
7
0
Order By: Relevance
“…7 Prior research conducted both before and after the FCIM guidelines suggests that training on these topics has been inadequate. [8][9][10][11][12][13][14] The University of Pittsburgh has a 187 well-established Section of Women's Health in the Division of General Internal Medicine and therefore provides many educational experiences that pertain to the care of women to all internal medicine residents in the program. However, through informal discussion with faculty, residents, and recent graduates we found that despite this strong women's health emphasis, there seemed to be a dearth of educational opportunities that specifically pertain to the internal medicine issues that women who are or who plan to become pregnant face.…”
mentioning
confidence: 99%
“…7 Prior research conducted both before and after the FCIM guidelines suggests that training on these topics has been inadequate. [8][9][10][11][12][13][14] The University of Pittsburgh has a 187 well-established Section of Women's Health in the Division of General Internal Medicine and therefore provides many educational experiences that pertain to the care of women to all internal medicine residents in the program. However, through informal discussion with faculty, residents, and recent graduates we found that despite this strong women's health emphasis, there seemed to be a dearth of educational opportunities that specifically pertain to the internal medicine issues that women who are or who plan to become pregnant face.…”
mentioning
confidence: 99%
“…The GCC specifies that every program must provide its fellows with comprehensive training in women's health; however, it provides little guidance on how to meet this goal. In addition to absence of an implementation plan, lack of exposure to appropriate patient populations (e.g., pregnant patients), deficits in knowledge at the faculty level, 23 and poor multidisciplinary collaboration 24 all create barriers to meeting training goals. By making crossdepartment alliances, we were able to expand our consultative services to include a greater number of women's health issues and to enlist non-GI faculty in the training of our fellows.…”
Section: Discussionmentioning
confidence: 99%
“…8 Not only is residency knowledge on HT lacking; studies also show even IM residents lacking in overall contraception knowledge. 25 Even among IM facility there have been reports that knowledge and procedural skills needed to teach necessary WH skills are lacking, 12 again pointing toward the functionality for WH fellowship-trained physicians to function in the gray zone between OB/GYN and IM. 22 Experiential learning on HT and other WH issues through training with fellowship-trained accredited leaders may be one way in which patient care is enhanced and practice patterns are changed for the better.…”
Section: Value Of Accreditationmentioning
confidence: 99%
“…10,11 Meanwhile, while medical school and residency exposure to WH outside the lens of obstetrics and gynecology is lacking, 8 the demand for WH providers is increasing, 1 and thus the need to raise awareness of WH fellowships is of optimal importance in order to train experts and educational leaders. 12 Unfortunately, the knowledge of these specialty interdisciplinary WH fellowships is lacking. 13 To evaluate the current national awareness of WHF programs, a study was conducted by sending surveys to family practice (FP) and IM residents across the United States.…”
mentioning
confidence: 99%